A Bibliometric Analysis of Sharia Bonds (Sukuk) in Islamic Capital Market - Erna Apriani; Abdul Latif; Indra Permana (DPPM Universitas Pelita Bangsa, 2023)
Sharia bonds (Sukuk) are one of the products of the Islamic capital market; the development of Islamic bonds is rapid in countries where most of the population is Muslim, using Islamic law principles. This study systematically explores the development of Sharia bond research (Sukuk) in the Islamic capital market in the observation period for six years, namely from 2017 to 2022. Bibliometrics is a data analysis approach in this study using the VOSviewer application. Quantitative description is an analysis method used in this study to describe the econometric literature with a network visualization model on the topic to be discussed. The sample is obtained using the publish or perish application with data from Google Scholar and Scopus, so the data obtained is then sorted to become relevant sample data of 760 articles related to Sukuk in the Islamic capital market. The results of the first VOSviewer mapping are ten articles with the most citations, network visualization, overlay visualization, and density visualization, and there are five clusters between item relationships; the keyword